ENVIRONMENTAL ATTITUDE AND ENVIRONMENTALLY FRIENDLY PRODUCTS TOWARDS PURCHASE INTENTION OF TANIMBAR IKAT WOVEN GREEN PRODUCTS - Matrona Patricia Malindir; Arry Widodo; Mahir Pradana (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This study examines consumer behavior towards sustainable products, specifically investigating the influence of environmental attitudes and green product attributes on green purchase intention among Tanimbar Ikat Weaving consumers in Tanimbar Islands Regency. Employing a quantitative approach with Structural Equation Modeling-Partial Least Square (SEM-PLS) analysis through SmartPLS software, data were collected from 385 respondents selected via purposive sampling based on consumers who knew and had purchased Tanimbar woven products. The research tested direct relationships and moderating effects of premium price, education, and gender variables. Results revealed that environmental attitudes (β = 0.349; t = 5.306; p = 0.000) and green product attributes (β = 0.207; t = 3.014; p = 0.003) significantly and positively influence green purchase intention, with the model explaining 60.7% of the variance (R² = 0.607) and demonstrating strong predictive relevance (Q² = 0.539). However, the three moderating variables—premium price, education, and gender—did not significantly strengthen or weaken these relationships, indicating that environmental consciousness and product perception remain dominant factors regardless of demographic or economic considerations. These findings provide practical implications for traditional craft entrepreneurs in developing sustainability-based marketing strategies and empowering the local creative economy, while contributing to the sustainable development goals through cultural preservation and environmental conservation in Indonesia's eastern region.